1993
DOI: 10.1002/art.1780360407
|View full text |Cite
|
Sign up to set email alerts
|

Linkage studies of hla and primary sjögren's syndrome in multicase families

Abstract: Objective. To define the role of HLA–DR pheno‐type in the expression of primary Sjögren's syndrome (SS). Methods. A family study of Caucasian probands with definite primary SS was conducted. Relatives with features of primary SS were classified according to the Fox criteria. Several types of linkage analysis between primary SS and HLA haplotype (HLA–A, B, and DR) were performed. Results. A trend toward haplotype sharing between affected siblings was evident for definite/probable primary SS when analyzed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 25 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The authors proposed that pSS is likely a polygenic disorder resulting from several genes interacting with environmental factors. Some studies of pSS showed that it has a strong association with HLA-DR3 6,13,14. However, recent studies have suggested that pSS is a complex, polygenic disorder sharing common genetic determinants with related autoimmune diseases, such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) 14.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that pSS is likely a polygenic disorder resulting from several genes interacting with environmental factors. Some studies of pSS showed that it has a strong association with HLA-DR3 6,13,14. However, recent studies have suggested that pSS is a complex, polygenic disorder sharing common genetic determinants with related autoimmune diseases, such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) 14.…”
Section: Discussionmentioning
confidence: 99%